Caffeinated Nitric Oxide-releasing Lozenge Improves Cycling Time Trial Performance - Lee, J.; Kim, H. T.; Solares, G. J.; Kim, K.; Ding, Z.; Ivy, J. L. (International Journal of Sports Medicine, 2015)
Boosting nitric oxide production during exercise by various means has been found to improve exercise performance. We investigated the effects of a nitric oxide releasing lozenge with added caffeine (70 mg) on oxygen consumption during steady-state exercise and cycling time trial performance using a double-blinded randomized, crossover experimental design. 15 moderately trained cyclists (7 females and 8 males) were randomly assigned to ingest the caffeinated nitric oxide lozenge or placebo 5 min before exercise. Oxygen consumption and blood lactate were assessed at rest and at 50%, 65% and 75% maximal oxygen consumption. Exercise performance was assessed by time to complete a simulated 20.15 km cycling time-trial course. No significant treatment effects for oxygen consumption or blood lactate at rest or during steady-state exercise were observed. However, time-trial performance was improved by 2.1% (p<0.01) when participants consumed the nitric oxide lozenge (2 424±69 s) compared to placebo (2 476±78 s) and without a significant difference in rating of perceived exertion. These results suggest that acute supplementation with a caffeinated nitric oxide releasing lozenge may be a practical and effective means of improving aerobic exercise performance.
Keywords: beetroot juice; nitrate; oxygen efficiency; nitrite; steady-state exercise